The effect of different ankle support devices on handball - Popovic , N. (Education. Physical training. Sport)
We evaluated the effect of different ankle support devices on the hand-ball performance in the group of 30 male handball players from the present Belgian cup winner. Four typical events for hand-ball players were selected 20 m. sprint, 20 m. slalom with the ball, 20 m. defence exercise and 20 m attack exercise. Each event was performed two times with the following condition: no ankle protection, both ankles taped, both ankles in ankle support (Ligaflex TM ), and both ankles in ankle brace (Dynastab TM). Compared to the results when no support was used, ankle taping decreased performance in the sprint (+3.37%), in the slalom with the ball (+2.87%), in the defence exercise (+2.97%), and in the attack event (+3.79%). The ankle support (Ligaflex TM ) decrease performance in Sprint (+3.10%), in slalom with the ball (+1.76%), in the defence event (+2.09%) and in the attack exercise (+2.64%). The ankle brace (Dynastab TM ) resulted in a significantly higher decrease in performance sprint (+7.09%), slalom (+6.32%), defence exercise (+3.27%) and attack exercise (+5.45%). The decrease in performance resulting from ankle taping, ankle support, and ankle brace does not seem to be important in handball practice.